Morphological Study of Adult Male Worms of Schistosoma mansoni Sambon, 1907 by Scanning Electron Microscopy - José Roberto Machado-Silva; Reinalda Marisa Lanfredi; Delir Corrêa Gomes (Memorias do Instituto Oswaldo Cruz, 1997)
Tubercles, spines and sensory receptors are the most studied structures of adult male worms of Schistosoma mansoni isolated in other countries. The purpose of this investigation was to properly define these structures in Brazilian worms. Specimens 7-8 weeks after infection were recovered from albino SW mice and from a wild rodent (Nectomys squamipes) and processed for scanning electron microscopy studies. Photomicrographs of the anterior region with the aspects related to the outer and inner regions of both suckers were considered. The ventral portion of the middle region was represented by the anterior of gynaecophoric canal while the dorsal surface was studied in its ventral and dorsal regions mainly focusing the aspect of the tubercles, spines and sensorial papillae. The outer surface of the oral sucker is spiny and spines are bigger, sharp with sensory receptors in their posterior edge. Tubercles with spines or receptors are more concentrated in the middle region and in one of the margins of the gynaecophoric canal. An excretory pore-like structure in the posterior portion was observed. The gynaecophoric canal has few sensory structures, spines broadned in their mid-region and are sharp pointed at the distal end. It was concluded that the presently studied characters are similar to those previously reported